Sterility problems of batch biotransformation of glycerol to dihydroxy acetone using immobilized gluconobacter oxydans - Raška, Jiří; Skopal, František; Komers, Karel; Machek, Jaroslav; Stloukal, Radek (Univerzita Pardubice, 2006)
Biotransformation of glycerol to dihydroxyacetone by the bacteria strain Gluconobacter oxydans immobilized in polyvinylalcohole gel has been studied. The sterility requirements necessary for successful course of reaction were examined. Suitable purity and treatment of reactor and all initial reaction components (water, glycerol, yeast extract, the air used for bacteria respiration and immobilized microorganisms) were found as necessary conditions against contamination.
Keywords: biotransformace; glycerol; mikroorganismy; sterilita